2020
DOI: 10.3892/ol.2020.11752
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes involved in the occurrence and development of hepatocellular carcinoma via bioinformatics analysis

Abstract: Hepatocellular carcinoma (HCC) is a heterogeneous malignancy, which is a major cause of cancer morbidity and mortality worldwide. Thus, the aim of the present study was to identify the hub genes and underlying pathways of HCC via bioinformatics analyses. The present study screened three datasets, including GSE112790, GSE84402 and GSE74656 from the Gene Expression Omnibus (GEO) database, and downloaded the RNA-sequencing of HCC from The Cancer Genome Atlas (TCGA) database. The differentially expressed genes (DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Next-generation sequencing (NGS) of the complete RNA transcriptome (RNA-seq) offers a novel approach to systematically characterize the underlying molecular mechanism of diseases. [39][40][41][42] In OR-6 cells treated with SOF 1uM for 24 hours, NGS study was performed and many genes were upregulated by SOF in OR-6 cells. Top-ranked genes were selected for further investigation (Table S1).…”
Section: Sof-upregulated Genes Were Associated With Cancer Developmenmentioning
confidence: 99%
“…Next-generation sequencing (NGS) of the complete RNA transcriptome (RNA-seq) offers a novel approach to systematically characterize the underlying molecular mechanism of diseases. [39][40][41][42] In OR-6 cells treated with SOF 1uM for 24 hours, NGS study was performed and many genes were upregulated by SOF in OR-6 cells. Top-ranked genes were selected for further investigation (Table S1).…”
Section: Sof-upregulated Genes Were Associated With Cancer Developmenmentioning
confidence: 99%
“…Deng et al found that PLK1 inhibition induces mitotic arrest at G2/M phase, leading to HCC cell apoptosis (25). Numerous findings based on bioinformatics confirmed that CDC20 might have a critical regulatory role in the occurrence and progression of HCC (26)(27)(28). Moreover, increased CDC20 was linked to poor prognosis of individuals with HCC (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that CDK1 and BUB1B were mainly involved in cell cycle regulation and cell movement ( 37 ). CCNB1 and CDC20 were identified as crucial genes associated with the pathogenesis and prognosis of pancreatic adenocarcinoma ( 38 ) and hepatocellular carcinoma ( 39 , 40 ). CCNB1 and CDC20 were indicated to be associated with cell cycle and cell proliferation and thus have an important role in tumor progression ( 41 ).…”
Section: Discussionmentioning
confidence: 99%